Bóg i człowiek w teologii zorientowanej dialogicznie - Składanowski, Marcin (Poznańskie Studia Teologiczne, 2013)
The idea of dialogue in philosophical and theological anthropology emphasizes the dignity proper to each human being as a person, and also the human social nature. In the 20th century many humanists rediscovered the idea of interpersonal dialogue. In the philosophical thought this idea is present in the works of Jewish thinkers: Martin Buber, Franz Rosenzweig and Emmanuel Levinas. But the notion of dialogue can also be useful in Chrisitian theological language. The article looks at the notion of dialogue in the definition of the relationship between God and human beings from the perspective of Christian Personalism. A “dialogically oriented theology” shows the relationship between God and man as a dialogue based on divine grace. The dignity of every human person is rooted in the vocation to dialogue with the persons of the Holy Trinity. This dialogue with God defines human beings in their relation to the world. The dialogue goes far beyond everyday life and finds its fulfillment in eternal dialogue with God and with the community of the redeemed.